Understanding the drivers, scale and impact of abandoned, lost and otherwise discarded fishing gear in small-scale fisheries: an Eastern Caribbean perspective - Lovell, Tricia A. (Frontiers in Marine Science, 2023)
Abandoned, lost and otherwise discarded fishing gear (ALDFG) presents a significant and complex challenge which can result in severe deleterious impacts to habitats, marine wildlife, and fishing and coastal communities the world over. Small island states like the countries of the Eastern Caribbean are highly vulnerable to a range of external stressors, therefore it is essential to gain an understanding of the threat posed by all forms of marine debris including ALDFG to the sub-region. To gain an understanding of the drivers, scale and impact of the threat associated with small-scale fisheries of the Eastern Caribbean, interviews with 49 fish trap and line fishers as well as 14 divers in Antigua and Barbuda, and Dominica were conducted. Interviews were completed over the course of two months (July – August 2022) at landing sites around all three islands. Fish traps continue to be a major contributor to ALDFG in the study area, with an estimated 2, 273 traps and 2, 567 being lost on Antigua and Barbuda, and Dominica respectively, based on the most recent estimates of the fishing fleet. Severe weather and snagging of benthic obstructions have emerged as the most significant contributors to fish trap loss in both countries while towing of fishing lines was the most frequently identified cause in the countries’ line fisheries. Observed variabilities in drivers of loss between both countries may be attributed to a number of factors including diversities in the fishing sectors, differences in local practices and heterogeneity in the biogeography of the marine environment. Further, evidence shows that the challenge of ALDFG within the Eastern Caribbean context, goes beyond local drivers of loss and may be influenced by transboundary inputs from both within and outside the region. Divers reported encountering not only ALDFG originating from within the two countries but some forms of ALDFG that may have drifted into the area from neighbouring islands (MFAD components) or further afield (polypropylene netting). Managing this challenge effectively will require not only fisheries specific interventions but the cooperation and collaboration of pool of stakeholders both nationally and beyond.